Inorganic electrochromic transistors as environmentally adaptable photodetectors - Ng, Si En (2022)
Visual sensing involves the ability to extract critical information from the environment such as colors, shapes and sizes. While conventional photodetectors have demonstrated high photoresponsivity across various wavelengths, they do not display intrinsic adaptability to a dynamic environment. A distinctive feature of our eyes is how they adapt to different light conditions and switch in priority between performance parameters – color sensitivity during the day and high contrast sensitivity during the night. Here we demonstrate an electrochromic MoO3 based transistor which behaves as a photodetector capable of adapting to the environmental light conditions. The ability to sense is enabled by the transduction of optical information into electrical signals via photoconduction. The ability to adapt is enabled by the switching between two phases with distinct optoelectronic properties based on electrochromism. We leverage the coupling between electrochromic switching of MoO3 and photo-electrical transduction to implement sensitization and desensitization of color detection. Subsequently, adaptation characteristics such as photopic and scotopic vision is demonstrated. Eschewing the need for bulky optics and central processing, the proposed electrochromic transistor offers significant advantages in miniaturization of adaptable photodetectors.